Early juristic approaches to the application of hiyal (legal devices) in Islamic law - Sadique, Muhammad Abdurrahman (International Islamic University Malaysia, 2008)
A precise demarcation separating hiyal from normal application of law has remained challenging. The majority of juristic trends are seen to categorize hiyal into permissible and impermissible types. Out of four categories of hiyal, juristic difference is found only with regard to one, where a permissible avenue is employed for attaining an unlawful end. This highlights that there is a large area of hiyal where there is near unanimity on acceptability. Despite the apparent laxity perceived of Hanafi jurists with regard to hiyal, they have limited the employment of hiyal to justifiable purposes only. The debate on hiyal could essentially be reduced to the juristic difference on the relevance and significance of intent in contracts, as upheld by Ibn Hajar al-'Asqalani.